2013
DOI: 10.1089/dna.2012.1928
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Functional Polymorphisms in Matrix Metalloproteinase 9 on Survival of Breast Cancer Patients in a Chinese Population

Abstract: Matrix metalloproteinase 9 (MMP9) plays a critical role in cancer aggression, and its overexpression is associated with a poor prognosis in breast cancer. Because common genetic variants can alter the expression or function of MMPs, we hypothesized that potentially functional single-nucleotide polymorphisms (SNPs) in the MMP9 gene may be associated with the survival of patients with invasive breast cancer. In this case-cohort follow-up study, a total of 245 breast cancer patients in southeast China were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…We conducted a subtype-specific GWAS, unlike other previous studies that had conducted a GWAS for overall breast cancer before stratifying by ER, PR, and HER2 status because breast cancer is considered as a heterogeneous disease for which the prognosis varies across subtypes[ 34 ]. This intertumor heterogeneity is plausible in that breast cancer could originate from different cell types according to the tumor subtype[ 35 ] and is supported by previous studies showing the heterogeneous associations between SNPs and the prognosis of breast cancer by ER, PR and HER2 status[ 15 , 18 27 ], in agreement with the current study ( Fig 2 ). Another reason for the subtype-specific analyses was that breast cancer subtypes are considered as a predictor factor that distinguishes different responses to particular therapies among patients[ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…We conducted a subtype-specific GWAS, unlike other previous studies that had conducted a GWAS for overall breast cancer before stratifying by ER, PR, and HER2 status because breast cancer is considered as a heterogeneous disease for which the prognosis varies across subtypes[ 34 ]. This intertumor heterogeneity is plausible in that breast cancer could originate from different cell types according to the tumor subtype[ 35 ] and is supported by previous studies showing the heterogeneous associations between SNPs and the prognosis of breast cancer by ER, PR and HER2 status[ 15 , 18 27 ], in agreement with the current study ( Fig 2 ). Another reason for the subtype-specific analyses was that breast cancer subtypes are considered as a predictor factor that distinguishes different responses to particular therapies among patients[ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…In 2013, a study evaluated MMP9 gene polymorphism as a potential biomarker to predict breast cancer prognosis in Chinese women. The authors found that carriers of the rs3787268 GA + AA genotype and rs17577 GG genotype showed significantly reduced survival rates among breast cancer patients with ER (+) and Her-2 (-) 20 . Our results suggested that the G allele of rs17577 had a protective effect compared with the A allele; this finding conflicts with the findings of the breast cancer study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on 245 Chinese women with invasive breast cancer, Fu et al ( 14 ) showed no correlation between MMP-9 rs17576 variant and survival free from locoregional disease and distant metastasis. Similarly, in a meta-analysis review, including ten articles evaluating MMP-9 polymorphic variants, Zhang et al ( 17 ) found that the MMP-9 rs17576 polymorphism had been evaluated in only three studies and had demonstrated no association between this SNP locus and changes in breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%